Implementation of Digital-Based Media through Podcast Projects in Developing Speaking Skills - Lintang Fatihatur Rohmah; Arisni Kholifatu Amalia Shofiani (Raja Zulkarnain Education Foundation, 2026)
his study aims to examine the effect of implementing digital media through a podcast-based project on students’ speaking skills. The research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. The participants were students from a selected educational institution who took part in speaking skills instruction through a podcast project. Data were collected using speaking skill tests administered before and after the treatment. The data were analyzed using descriptive and inferential statistics, specifically a paired-sample t-test. The results revealed an improvement in students’ speaking skills after the implementation of the podcast-based project. The mean score of the pretest was 77.64, which increased to 86.16 in the posttest, indicating a gain of 8.52 points. Statistical analysis demonstrated a significant difference between pretest and posttest scores at a significance level of a = 0.05. These findings indicate that the use of digital media through podcast projects has a positive effect on enhancing students’ speaking skills. Therefore, podcast-based digital media can be considered an effective alternative for teaching speaking skills. Learning through podcast projects encourages active participation, creativity, and students’ confidence in expressing ideas orally, making the learning process more meaningful and relevant to digital-era education.